(untitled) (Research, Society and Development, 2021)
Family farming is characterized by the insertion of small family producers in agricultural units, who establish different cultures, on small properties of land, using rudimentary technology and family labor, allocating their production for self-consumption. From this perspective, the goal was to represent the environmental and socioeconomic aspects of rural family producers in the mid-region of Parnaíba in Piauí, so that such information could serve as a subsidy in decision-making in the rural space. The research was conducted in four rural locations, through semi-structured interviews, totaling 44 informants, and the collected data were analyzed using the mixed approach method. It was found that the interviewed farmers are mostly male (39 individuals), of adult age (54.54%) and of low education (54.54%). In terms of family income, earnings from agriculture do not reach a minimum wage for 47.72% of the participants. Among the factors associated with the rural exodus, the following can be highlighted: search for improvements in living conditions, water scarcity and the advancement of agribusiness, especially in the upper river course. It was inferred that low education directly reflects on the monthly income perceived by rural family farmers, which consequently has an impact on the infrastructure of their production site, on the mechanisms of land use and management, as well as on the income of the products obtained, thus denoting strong correlation between socioenvironmental variables and the mode of agricultural development performed by the small rural producer.